2021
DOI: 10.3390/e23121677
|View full text |Cite
|
Sign up to set email alerts
|

The Downside of Heterogeneity: How Established Relations Counteract Systemic Adaptivity in Tasks Assignments

Abstract: We study the lock-in effect in a network of task assignments. Agents have a heterogeneous fitness for solving tasks and can redistribute unfinished tasks to other agents. They learn over time to whom to reassign tasks and preferably choose agents with higher fitness. A lock-in occurs if reassignments can no longer adapt. Agents overwhelmed with tasks then fail, leading to failure cascades. We find that the probability for lock-ins and systemic failures increase with the heterogeneity in fitness values. To stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Using non-network approaches, the authors of [39] characterised the interaction structure spatially by detecting locations in an o ce building where employees frequently interact. In other works, the task redistribution between software developers was studied with agent-based models [12,30]. The key di erence to this work is that all approaches mentioned above study the interaction structure between individuals.…”
Section: Related Workmentioning
confidence: 99%
“…Using non-network approaches, the authors of [39] characterised the interaction structure spatially by detecting locations in an o ce building where employees frequently interact. In other works, the task redistribution between software developers was studied with agent-based models [12,30]. The key di erence to this work is that all approaches mentioned above study the interaction structure between individuals.…”
Section: Related Workmentioning
confidence: 99%
“…It helps understanding cascading effects from removing a specific agent. Centralization [179] takes the concentration of interactions in a few agents into account, which increases the systemic risk if these agents fail [34] (see also Figure 17). Betweenness preference [128] and Eigengap [112] indicate communication bottlenecks and identify gate keepers.…”
Section: Quantifying Social Resiliencementioning
confidence: 99%
“…Their integration into the collective may improve over time, as can be 27/54 measured by their coreness [58,151,155]. If core nodes leave, this may trigger cascades of other nodes leaving as empirical and simulation studies have demonstrated [34,60].…”
Section: Dynamics Of Social Organizationsmentioning
confidence: 99%
“…It helps understanding cascading effects from removing a specific agent. Centralization [179] takes the concentration of interactions in a few agents into account, which increases the systemic 32/54 risk if these agents fail [34] (see also Figure 17). Betweenness preference [128] and Eigengap [112] indicate communication bottlenecks and identify gate keepers.…”
Section: Quantifying Social Resiliencementioning
confidence: 99%